An Efficacy of Seligi Leaf Flour Fermentation on Cholesterol Levels, Low Density Lipoprotein, and High Density Lipoprotein in Catfish - Hardiansyah, Reza; Lamid, Mirni (Jurnal Medik Veteriner, 2022)
Catfish is a freshwater fish with a high economic value, so it is very good to be developed. Feed is one of the most important components in the cultivation process because it plays a role in supporting the plants and the survival of cultivated fish. Seligi (Phyllanthus buxifolius) is a native Indonesian medicinal plant that has been widely used for medicinal purposes. Seligi leaf extract is known to contain flavonoids, polyphenols (tannins), saponins, alkaloids, quinones, and triterpenoid steroids. The purpose of this research was to determine the effect of using fermented seligi leaf flour in feed to reduce levels of total cholesterol, low-density lipoprotein, and high densities lipoprotein in catfish meat. The method used in this research is the experimental method. The main parameters in this study were total cholesterol, low-density lipoprotein (LDL), and high-density lipoprotein (HDL) in catfish meat. The supporting parameters in this research are water quality which includes temperature, pH, dissolved oxygen (DO), and ammonia (NH3-N). The results showed that the total cholesterol content of catfish meat ranged from 116.84-233.65 mg/dL. Meanwhile, the results of LDL in catfish meat ranged from 37.89-74.22 mg/dL. Then, the content of HDL in catfish meat ranges from 89.25-225.87 mg/dL.